Capture Order Across Social Bathyergids Indicates Similarities in Division of Labour and Spatial Organisation - Zöttl, Markus; Bensch, Hanna M.; Finn, Kyle T.; Hart, Daniel W.; Thorley, Jack; Bennett, Nigel C.; Braude, Stan (Frontiers in Ecology and Evolution, 2022)
1) Abstract The social mole-rats of the family Bathyergidae show elaborate social organisation that may include division of labour between breeders and non-breeders as well as across non-breeders within their groups. However, comparative behavioural data across the taxa are rare and contrasts and similarities between species are poorly understood. Field studies of social bathyergids usually involve capturing all group members until the entire group is captured. Because each animal is only captured once and traps are typically placed in close proximity to active foraging areas, the order in which animals are captured provides an indication of the foraging activity of different individuals and of the spatial organisation of the group within the burrow system. Here, we compare the association of capture order with breeding status, sex and body mass in four species and subspecies of social bathyergids, which vary in group size and represent all three social genera within the family Bathyergidae. We show that in naked and Damaraland mole-rats (Heterocephalus glaber and Fukomys damarensis), male and female breeders are captured later than non-breeders, whereas in two different subspecies of the genus Cryptomys only female breeders are captured later than non-breeders. The effect sizes vary largely and are 10 times larger in naked mole-rats as compared to Fukomys and 3-4 times larger than in Cryptomys. Among non-breeders, sex effects are notably absent in all species and body mass predicted capture order in both naked and Damaraland mole-rats. In naked mole-rats, larger non-breeders were captured earlier than smaller ones, whereas in Damaraland mole-rats intermediate-sized non-breeders were captured first. Our data suggest that there are similarities in behavioural structure and spatial organisation across all social bathyergid species, though the most pronounced differences within groups are found in naked mole-rats.